2009
DOI: 10.1017/s0020818309090031
|View full text |Cite
|
Sign up to set email alerts
|

Rage Against the Machines: Explaining Outcomes in Counterinsurgency Wars

Abstract: During the nineteenth century, states routinely defeated insurgent foes+ Over the twentieth century, however, this pattern reversed itself, with states increasingly less likely to defeat insurgents or avoid meeting at least some of their demands+ What accounts for this pattern of outcomes in counterinsurgency~COIN! wars? We argue that increasing mechanization within state militaries after World War I is primarily responsible for this shift+ Unlike their nineteenth-century predecessors, modern militaries posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
282
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(294 citation statements)
references
References 39 publications
8
282
1
3
Order By: Relevance
“…An overview of these cases is given in Table 3. The GED analysis was restricted to cases of irregular war and identified through a dataset of insurgencies by Lyall and Wilson (2009). As mentioned previously, the wider coverage of the GED data comes at a price: initiators of violence are not coded, and the type of violence for the conflict events is not disaggregated into tactical categories.…”
Section: Civilian Casualties In African Insurgenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…An overview of these cases is given in Table 3. The GED analysis was restricted to cases of irregular war and identified through a dataset of insurgencies by Lyall and Wilson (2009). As mentioned previously, the wider coverage of the GED data comes at a price: initiators of violence are not coded, and the type of violence for the conflict events is not disaggregated into tactical categories.…”
Section: Civilian Casualties In African Insurgenciesmentioning
confidence: 99%
“…While this distinction has been made before (see Mason and Krane, 1989), Kalyvas's (2006) widely cited study brought increased scholarly attention to the study of violence in civil wars, resulting in numerous publications (e.g. Condra and Shapiro, 2012;Downes, 2007;Lyall, 2009;Lyall and Wilson;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallensteen (2015), Fortna (2009) and Lyall and Wilson (2009), have long argued that outrights victories have become increasingly rare in civil wars, and conclude that these outcomes have been replaced by negotiated compromises. Meanwhile, contrary to assumptions in the literature, emerging studies have shown that wars do not exclusively end with decisive outcomes such as victories or negotiated settlements but more often end under unclear circumstances in which fighting simply ceases or disappears (Kreutz, 2012).…”
Section: Military Victoriesmentioning
confidence: 99%
“…6 Without knowing where the rebels are, the state cannot take advantage of its initial military superiority (Kalyvas, 2006: 174;Leites and Wolf, 1970: 33). This is amply shown in the counterinsurgency literature, which points to information-gathering abilities as the most important determinant of counterinsurgent effectiveness (Lyall and Wilson, 2009;Lyall, 2010).…”
Section: The Politico-military Opportunity Explanationmentioning
confidence: 99%